Comparison of clinicopathological characteristics and prognosis between primary squamous cell carcinoma of the thyroid and squamous cell carcinoma combined with papillary thyroid carcinoma - Yan, Wanyun; Chen, Huiying; Lin, Xiaoyu; Zhou, Ruifa; Zhao, Feng; Su, Jiping (Frontiers in Endocrinology, 2025)
BackgroundPrimary squamous cell carcinoma of the thyroid (PSCCT) has recently been reclassified as a morphologic pattern of anaplastic thyroid carcinoma (ATC). Consequently, PSCCT and squamous cell carcinoma with papillary thyroid carcinoma (SCC-PTC) were categorized as ATC. However, in terms of clinical characteristics and overall prognosis, whether PSCCT is similar to SCC-PTC has yet to be sufficiently investigated. Therefore, this study aimed to elucidate the differences and similarities between PSCCT and SCC-PTC regarding clinicopathological characteristics and prognosis.MethodsWe retrospectively reviewed the medical records of patients with squamous cell carcinoma of the thyroid in our institution from December 2009 to December 2020. In addition, the publications in CNKI, Wanfang, VIP, PubMed, Embase, Web of Science, and ProQuest databases were systematically searched to collect patient information. According to pathological diagnosis, patients were divided into the PSCCT and SCC-PTC groups, and compared their clinical characteristics, treatment, and prognosis, respectively.Results308 patients in the PSCCT group and 60 patients in the SCC-PTC group were enrolled in the study. There were significant differences in gender, age, T stage, N stage, M stage, symptoms at diagnosis, and TTF-1 expression between the two groups. Patients in the SCC-PTC group with more frequent radioactive iodine therapy, surgery, and less frequent radiotherapy than PSCCT. In addition, PSCCT and SCC-PTC also demonstrated similarities in tracheal invasion, esophageal invasion, CK5/6 expression, TG expression, P53 expression, and chemotherapy frequency. The 3-year overall survival rate of PSCCT (19.1%) was lower than that of SCC-PTC (34.6%). The prognostic factors were different between the two groups. Multivariable analysis shows that the N stage, M stage, radiotherapy, and tracheal invasion were related to the prognosis of PSCCT, while only the T stage was associated with the prognosis in SCC-PTC.ConclusionsClinicopathological characteristics and prognosis were not identical in patients with SCC-PTC and PSCCT. These findings indicated that different clinical treatment and management plans are required for patients with these two types of thyroid cancer.